Etnoarqueología del Bajo Rímac y el Callao prehispánico - Silva Sifuentes, Jorge (2005)
The purpose of this article is to provide a discussion about late period prehispanic occupations of the lower Rímac River Valley based on pottery remains found in the La Perla district. Following this purpose, two issues are assessed. First, the faster destruction of small constructions compared with large architectural buildings. Second, Late Intermediate and Late Horizon periods tend to be studied either from the ethnohistoric or from the archaeological perspectives. Finally, it is remarked that a better understanding of these periods will be possible by combining ethnohistoric sources and archaeological data.